2022
DOI: 10.1186/s12875-022-01628-8
|View full text |Cite
|
Sign up to set email alerts
|

Bio-psycho-social characteristics and impact of musculoskeletal pain in one hundred children and adolescents consulting general practice

Abstract: Background Eight percent of all child and adolescent general practice consultations are due to musculoskeletal conditions, with pain as the most frequent symptom. Despite the commonality of musculoskeletal pain, limited knowledge exists about care-seeking children and adolescents with musculoskeletal pain. The purpose of this study was to describe characteristics of children and adolescents consulting their general practitioner with musculoskeletal pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…[3] MSK pain in childhood can impact children's daily activities. [4,5] For example, frequent pain can lead to school absenteeism, [6] decreased social interaction and quality of life, [7,8] and activity limitations. [9] Importantly, the impact of MSK pain may track into adulthood, suggesting that mitigating pain and its impact on childhood could have lifelong consequences.…”
Section: Introductionmentioning
confidence: 99%
“…[3] MSK pain in childhood can impact children's daily activities. [4,5] For example, frequent pain can lead to school absenteeism, [6] decreased social interaction and quality of life, [7,8] and activity limitations. [9] Importantly, the impact of MSK pain may track into adulthood, suggesting that mitigating pain and its impact on childhood could have lifelong consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Between the age of 12 and 15 years, musculoskeletal complaints are the fourth most common cause for consulting general practice [ 4 ]. The most common pain site is the knee, accounting for between 30% and 50% of all presentations in this age group [ 5 ]. Previously, knee pain was considered to be benign and self-limiting [ 6 ], but recent studies have demonstrated that 40% to 50% of adolescents still struggle with pain after 2 to 5 years [ 7 ], and 7 out of 10 had reduced or halted their sports participation owing to knee pain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…From our 3 studies we found that musculoskeletal pain is prevalent among children and adolescents 1,2,3 , a significant proportion feel nervous or anxious 2 , and more than half worry about their cause of pain 2,3 . Our understanding of adolescents' pain experience beyond worries was rather limited, however, if fear avoidance behavior persists it may facilitate transition towards chronic pain, indicating that pain cause more than just physical limitations 4 .…”
Section: Prognosis and Prognostic Factors For Long-term Musculoskelet...mentioning
confidence: 87%
“…NP made first contact with the entire sample frame upon recruitment for the ChiBPS study more than two years prior to study 4 2,3 . NP introduced the adolescents to study 4 without requiring a definite yes/no to participation, thus avoiding either 1) a quick and easy yes from someone who had not yet actually met the interviewer or 2) a defensive no because of too much initial pressure 85 .…”
Section: Interview Guide Studymentioning
confidence: 99%
See 1 more Smart Citation